Using Filmed Expert Demonstrations in Counsellor Education: Suggestions and Recommendations - Keats, Patrice A. (Canadian Journal of Counselling and Psychotherapy, 2009)
Although research exists about student learning processes using filmed experts demonstrating counselling systems and skills, there appears to be no formal direction or advice for instructors or supervisors on how to view, use, or teach with these types of films. This article attempts to fill this gap by combining ideas from the literature on pedagogical uses of visual media in education, student suggestions about film use, and experiences of instructors using expert demonstration films. Effective practices are suggested, including preparing students for viewing, understanding viewing processes, and post-viewing discussion techniques.